A Novel Concentric Annular-Ring Slot Dual-Band Circularly Polarized Microstrip Antenna - Yong Cheng; Hui Liu (International Journal of Antennas and Propagation)
A simple structure concentric annular-ring slot dual-band circularly polarized (CP) microstrip antenna operating at ISM band (2.45 GHz) and 5G band (3.5 GHz) is proposed in this paper. The antenna achieves dual-band operation by digging two concentric annular-ring slots on the ground. And on the angular positions with 45 degrees inclined of each annular slot, two bent structures are loaded to generate circularly polarized radiation. The radiation of this antenna is bidirectional, and the directions of rotation are opposite. The measured results of the annular-ring slot microstrip antenna show good performance of dual-band circularly polarized characteristics.